Acinetobacter baumannii infections in the paediatric intensive care unit of a tertiary hospital in South Africa - Reddy, Deveshnee (Department of Paediatrics and Child Health, 2015)
Acinetobacter baumannii (A. baumannii) is now increasingly recognised as an important cause of nosocomial infections in paediatric intensive care unit (PICU) patients, particularly in developing countries, where it contributes significantly to morbidity and mortality. Furthermore, it has been documented that emerging antimicrobial resistance patterns complicate antibiotic choice in these patients. At present, more paediatric data is needed regarding these infections. This is a retrospective case-control study that aims to document the demographic data and relevant clinical details of patients in whom A. baumannii was cultured, either from blood or respiratory specimens (thus including both infections and colonisation), in the PICU at Red Cross War Memorial Children's Hospital (RCWMCH) during 2010. Secondary objectives include comparing these patients with those in whom A. baumannii was not cultured and determining which isolates were causing infection and which were colonisers. In addition; of the isolates regarded as infections, documenting the antimicrobial sensitivities and resistance of the organisms cultured, determining whether infections were late or early onset and determining whether specific bed numbers were consistently involved.